Osteocyte-mediated mechanical response controls osteoblast differentiation and function - Buck, Heather VerValin; Stains, Joseph Paul (Frontiers in Physiology, 2024)
Low bone mass is a pervasive global health concern, with implications for osteoporosis, frailty, disability, and mortality. Lifestyle factors, including sedentary habits, metabolic dysfunction, and an aging population, contribute to the escalating prevalence of osteopenia and osteoporosis. The application of mechanical load to bone through physical activity and exercise prevents bone loss, while sufficient mechanical load stimulates new bone mass acquisition. Osteocytes, cells embedded within the bone, receive mechanical signals and translate these mechanical cues into biological signals, termed mechano-transduction. Mechano-transduction signals regulate other bone resident cells, such as osteoblasts and osteoclasts, to orchestrate changes in bone mass. This review explores the mechanisms through which osteocyte-mediated response to mechanical loading regulates osteoblast differentiation and bone formation. An overview of bone cell biology and the impact of mechanical load will be provided, with emphasis on the mechanical cues, mechano-transduction pathways, and factors that direct progenitor cells toward the osteoblast lineage. While there are a wide range of clinically available treatments for osteoporosis, the majority act through manipulation of the osteoclast and may have significant disadvantages. Despite the central role of osteoblasts to the deposition of new bone, few therapies directly target osteoblasts for the preservation of bone mass. Improved understanding of the mechanisms leading to osteoblastogenesis may reveal novel targets for translational investigation.